2012
DOI: 10.1088/0266-5611/28/11/115003
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic elastic moduli reconstruction in transversely isotropic model using MRE

Abstract: Magnetic resonance elastography (MRE) is an elastic tissue property imaging modality in which the phase-contrast based MRI imaging technique is used to measure internal displacement induced by a harmonically oscillating mechanical vibration. MRE has made rapid technological progress in the past decade and has now reached the stage of clinical use. Most of the research outcomes are based on the assumption of isotropy. Since soft tissues like skeletal muscles show anisotropic behavior, the MRE technique should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…61,62 Others proposed the use of a linear (visco) elastic transverse isotropic material approach as an intermediate solution. [63][64][65][66] Using this approach, Qin et al found a decrease in anisotropic ratio, related to necrosis, in an MDX mouse model of diseased skeletal muscle. 67 However, to date the transverse isotropic MRE inversion is still rarely used, as muscle fiber directions obtained, for example by diffusion tensor imaging (DTI), are needed as input.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…61,62 Others proposed the use of a linear (visco) elastic transverse isotropic material approach as an intermediate solution. [63][64][65][66] Using this approach, Qin et al found a decrease in anisotropic ratio, related to necrosis, in an MDX mouse model of diseased skeletal muscle. 67 However, to date the transverse isotropic MRE inversion is still rarely used, as muscle fiber directions obtained, for example by diffusion tensor imaging (DTI), are needed as input.…”
Section: Resultsmentioning
confidence: 99%
“…Although this approach is used by several groups, it is a simplification for skeletal muscle which generally exhibits nonlinear viscoelastic anisotropic material behavior . Others proposed the use of a linear (visco) elastic transverse isotropic material approach as an intermediate solution . Using this approach, Qin et al found a decrease in anisotropic ratio, related to necrosis, in an MDX mouse model of diseased skeletal muscle .…”
Section: Discussionmentioning
confidence: 99%
“…Although significant progress has been made in the development of shear modulus imaging technology, problems remain image quality relating to the enhancement of images of local tissue shear viscosity and shear modulus [10,13,15,19,29,30,31,35]. This paper focuses on the image reconstruction methods for tissue viscoelasticity imaging.…”
Section: Introductionmentioning
confidence: 99%
“…78 One of the main limitations of MR elastography of the muscle is that the stiffness is still assessed with a manual technique, which could show subjective variation, but ongoing work in this domain may address this issue in the near future. 79 …”
Section: Quantitative Mr Imaging Techniquesmentioning
confidence: 99%